Vacuolar processing enzyme in plant programmed cell death - Hatsugai, Noriyuki; Yamada, Kenji; Goto-Yamada, Shino; Hara-Nishimura, Ikuko (Frontiers in Plant Science, 2015)
Vacuolar processing enzyme (VPE) is a cysteine proteinase originally identified as the proteinase responsible for the maturation and activation of vacuolar proteins in plants, and it is known to be an orthologue of animal asparaginyl endopeptidase (AEP/VPE/legumain). VPE has been shown to exhibit enzymatic properties similar to that of caspase 1, which is a cysteine protease that mediates the programmed cell death (PCD) pathway in animals. Although there is limited sequence identity between VPE and caspase 1, their predicted three-dimensional structures revealed that the essential amino-acid residues for these enzymes form similar pockets for the substrate peptide YVAD. In contrast to the cytosolic localization of caspases, VPE is localized in vacuoles. VPE provokes vacuolar rupture, initiating the proteolytic cascade leading to PCD in the plant immune response. It has become apparent that the VPE-dependent PCD pathway is involved not only in the immune response, but also in the responses to a variety of stress inducers and in the development of various tissues. This review summarizes the current knowledge on the contribution of VPE to plant PCD and its role in vacuole-mediated cell death, and it also compares VPE with the animal cell death executor caspase 1.